2020
DOI: 10.1111/epi.16525
|View full text |Cite
|
Sign up to set email alerts
|

Cenobamate (YKP3089) as adjunctive treatment for uncontrolled focal seizures in a large, phase 3, multicenter, open‐label safety study

Abstract: This is an open access article under the terms of the Creative Commons Attribution-NonCommercial License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited and is not used for commercial purposes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

17
215
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 128 publications
(233 citation statements)
references
References 25 publications
17
215
1
Order By: Relevance
“…Remarkably, the interim report from the ongoing phase III safety study provided dosing guidance for the real-world management of patients taking cenobamate and concomitant phenytoin or phenobarbital, who instead were excluded from the RCTs. In this study, which allows dose adjustment of concomitant ASMs based on the patient's clinical condition and plasma levels, around 45 and 30% of patients taking phenytoin and phenobarbital had their doses decreased [35]. At the end of the titration, the mean plasma levels of phenytoin and phenobarbital were generally comparable to those obtained before the start of cenobamate, suggesting that periodic dose reductions of 25-33% in response to AEs can be effective to maintain stable plasma levels [35].…”
Section: Pharmacological Interactionsmentioning
confidence: 74%
See 2 more Smart Citations
“…Remarkably, the interim report from the ongoing phase III safety study provided dosing guidance for the real-world management of patients taking cenobamate and concomitant phenytoin or phenobarbital, who instead were excluded from the RCTs. In this study, which allows dose adjustment of concomitant ASMs based on the patient's clinical condition and plasma levels, around 45 and 30% of patients taking phenytoin and phenobarbital had their doses decreased [35]. At the end of the titration, the mean plasma levels of phenytoin and phenobarbital were generally comparable to those obtained before the start of cenobamate, suggesting that periodic dose reductions of 25-33% in response to AEs can be effective to maintain stable plasma levels [35].…”
Section: Pharmacological Interactionsmentioning
confidence: 74%
“…Three of these events, including the case of DRESS, occurred early during treatment, at the start of the drug or during the titration schedule. During early clinical development, three confirmed cases of DRESS were also identified among the first 953 participants exposed to cenobamate, including one fatality [31]. Cutaneous, idiosyncratic AEs have been reported with ASMs.…”
Section: Summary Of Main Resultsmentioning
confidence: 95%
See 1 more Smart Citation
“…It has been demonstrated to reduce focal seizures in two phase 2 clinical studies (NCT01397968 and NCT01866111) compared to placebo [7,8]. In addition, an interim analysis of an ongoing open-label phase 3 safety study (NCT02535091) demonstrated safety and tolerability of cenobamate over a duration of approximately 6.5 months [9]. Cenobamate is prepared as an oral film-coated tablet that is soluble in water (1.7 mg/mL).…”
Section: Key Pointsmentioning
confidence: 99%
“…Relatively recently, two novel antiepileptic drugs (AEDs, cenobamate and perampanel, have been licensed and approved as add-on drugs to clinical practice by FDA in USA and EMA in the EU [1,2]. At present, physicians can prescribe for epileptic patients approx.…”
Section: Introductionmentioning
confidence: 99%